2014
DOI: 10.1186/s13054-014-0683-x
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal as a new biomarker in patients with septic shock: an observational clinical study

Abstract: IntroductionThe role of reactive carbonyl species, such as methylglyoxal (MG), has been overlooked within the context of the sepsis syndrome. The aims of this study were to assess the impact of MG formation in different inflammatory settings and to evaluate its use for early diagnosis as well as prognosis of the sepsis syndrome.MethodsIn total, 120 patients in three groups were enrolled in this observational clinical pilot study. The three groups included patients with septic shock (n = 60), postoperative cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…Furthermore, physicians are confronted with various individual comorbidities and other influencing factors [164] . Lately, Brenner et al [165] showed the involvement of alternative mediators of cellular stress in the pathophysiology of sepsis. Methylglyoxal (MG), which is one of these highly reactive carbonyl species, is produced endogenously from the spontaneous degradation of triosephosphates (glyceraldehyde-3-phosphate and dihydroxyacetone phosphate) during glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, physicians are confronted with various individual comorbidities and other influencing factors [164] . Lately, Brenner et al [165] showed the involvement of alternative mediators of cellular stress in the pathophysiology of sepsis. Methylglyoxal (MG), which is one of these highly reactive carbonyl species, is produced endogenously from the spontaneous degradation of triosephosphates (glyceraldehyde-3-phosphate and dihydroxyacetone phosphate) during glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with routine diagnostic markers, MGO is a more useful marker of sepsis onset, development, and remission [20]. Sepsis is an infection accompanied by a systemic inflammatory response to the infection; this response causes multi-organ dysfunction even in uninfected organ systems; these events frequently lead to death [56].…”
Section: Methylglyoxal and Sepsismentioning
confidence: 99%
“…However, direct measurement of tissue MGO requires biopsy or surgical tissue, and is not validated in humans. Plasma MGO levels, determined by HPLC, may prognosticate septic shock [20]. Testing MGO requires more clinical trials exploring its prognostic abilities and potential therapeutic applications.…”
Section: Methylglyoxal Usage In Clinical Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no biomarker can answer all questions alone with 100% sensitivity and specificity in severe sepsis and septic shock owing to the overlapping pathomechanism of PAMPs and DAMPs discussed in detail above [29].…”
Section: The Role Of Biomarkers At the Bedsidementioning
confidence: 99%